Rubella seroprevalence in childbearing age women: a cross sectional study in the province of Frosinone, Central Southern Ital (Italian Journal of Public Health, 2009)
Background: Congenital rubella infection can be prevented by protecting women of reproductive age throughvaccination. The aims of this study were to estimate the seroprevalence of rubella virus antibodies amongfemales aged between 15 and 45 years in the province of Frosinone and to assess knowledge about Rubellaand Congenital Rubella Syndrome (CRS) and the association between rubella immunization status andvarious risk factors.Methods: A cross sectional study was carried out involving 1242 females recruited by random selection.Enzyme immunoassay method was used to detect and quantify human anti IgG antibodies for rubella virus in1242 anonymously females aged between 15 and 45 years. A questionnaire was used to collect demographicdata including age, sex, previous history, previous vaccination and knowledge about rubella. Statisticalanalysis was carried out using the program EpiInfo 3.3.Results: The majority of the females recruited to the study were 15-24 years old (66%), unmarried (71.2%),students (61%) who had not previously given birth (87.9%). Rubella Seroprevalence was 90.3% in womenaged 40-45 years old and 68.8% in those aged 15-19 (p=0.0001). Only 137 participants reported havingreceived rubella vaccination. Generally knowledge about rubella and congenital rubella syndrome waslacking.Conclusions: In the province of Frosinone, women in each age group were in need of active immunization.Furthermore, the susceptibility rates for rubella are far from the value of national serosurveys for similar agegroups (8%) and even further from the target set by the National Plan for Measles and Congenital RubellaElimination launched in 2003. For females of reproductive age, immunization is an effective but underutilizedmethod of CRS prevention and although rubella vaccine is free charge for these women and pre-conceptionscreening is available, these opportunities remain substantially underutilised.
Keywords: rubella; seroprevalence; childbearing women; Italy